DERMATOGLYPHIC CHARACTERISTICS, SOMATOTYPE AND PHYSICAL QUALITIES IDENTIFICATION OF BRAZILIAN MILITARY PENTATHLON TEAM (Fiep Bulletin - online, 2014)
The present study aims to identify military pentathlon high level athletes profile about dermatogliphics, somatotype and physical qualities. In elaborating this work, six athletes from the Brazilian military team were observed. They competed in the last edition of the world championship of the Conseil International de Desports Militaires (CISM). The practical implication, in identifying the profile of military pentathlon athletes in Brazil, is incorporated with the needs of this sport modality, because Brazil is four times world champion of the CISM and this team needs to get younger. By the way, Brazil needs some data to find the new athletes and to develop new values in this sport. The group was submitted to an evaluation to identify the dermatoglyphic profile by means of digital impressions (DI), following the protocol of Cummins and Midlo (1942), to an evaluation of somatotype, by the anthropometric method of Heath-Carter (1967), and tests of some physical qualities: Coordination (Burpee Test - Johnson & Nelson, 1979); Speed (50 meters running - Johnson & Nelson, 1979); Legs power (Sargent Jump test - Johnson & Nelson, 1979); Arms power (Two Hand Medicine Ball Put - Johnson & Nelson,1979); Aerobic resistance (Léger-Boucher - Léger e Boucher,1980); Agility (Shuttle Run, Johnson & Nelson (1979); Flexibility (Seat and Reach Test, Johnson & Nelson (1979) and Anaerobic resistance (40 seconds running - Matsudo, 1979). In identifying the genetic profile, the characteristics of models of the Digital Impressions were elaborated for high performance, male, pentathlon athletes, that included the most informative and integral: D10= 9,20 ± 2,17; SQTL= 82,3 ± 42,34; L= 7,60 ± 1,52; W = 0,67 ± 0,52 e A= 1,33 ± 1,75, with high incidence of loop (L) and low incidence of whool (W). The predominant types of digital form were also established: AL = 16,7 %; L>W = 33,3 %, 10L = 16,7 % e ALW = 33,3 %. In identifying the somatotype profile, the characteristics of the group studied were presented following the three components of somatotype of Heath-Carter, which were: endomorphy = 1,51 ± 0,17; mesomorphy = 5,55 ± 1,03; and ectomorphy = 2,20 ± 0,57. These values characterize the group studied as meso-ectomorphyc. About the basic physical qualities, the results were: Coordination 16,67 +/- 0,52 parts, Speed 5,81 +/- sec, Legs power 59,33 +/- 6,46 cm, Arms power 5,08 +/- 0,21 cm, Aerobic resistance 66,47 +/- 3,25 ml (kg.min-1), Agility 9,03 +/- 0,17 sec, flexibility 52 +/- 4,11 cm ans Anaerobic resistance 296,50 +/- 4,04 m. The results applied to this team warranted the second place in the last Military Pentathlon World Championship in Chile.
Keywords: Dermatoglific profile; Somatotype; Physical qualities